A nonlinear full condition process monitoring method for hot rolling process with dynamic characteristic. (June 2021) - Zhang, Chuanfang; Peng, Kaixiang; Dong, Jie
Abstract: As a typical complex industrial process, hot rolling process (HRP) is different from chemical process. Strip steels are produced coil by coil, that means there is a long idle period between coils. The rolling speed is very high and the producing time of each coil is usually a few minutes. Previous researches mostly focus on fault detection in loaded condition and very few attempts have been made to exploit the monitoring of idle condition. In order to monitor the whole process, not only the loaded condition, but also the idle one, a novel nonlinear full condition process monitoring model is developed in this work. First, a dissimilarity index (DI) is defined for condition identification and a support data vector description (SVDD) model is established to monitor the idle condition. Second, t -distributed stochastic neighbor embedding ( t -SNE) is used to extract nonlinear principal components (NPC) for slow feature analysis (SFA) and cointegration analysis (CA). Nonlinear cointegration analysis (NCA) can reveal the long-run dynamic relations of nonstationary parts, while nonlinear slow feature analysis (NSFA) can extract the latent temporal dynamic and static variations of stationary ones. Finally, the monitoring performance of the proposed model is verified through a real HRP. Highlights: Commonly used data-driven methods, including t -SNE, CA, SFA are investigated. A novel dissimilarity index is proposed which can identify the process condition. A nonlinear CA is developed which can extract dynamic relations of variables. A nonlinear SFA model is developed to extract dynamic and static variations. Application in hot rolling process is carried out to show the theoretical results.